Implications of Supply Chain Management (SCM): Manufacturing Industries to Service supply Industries - Mamun Habib (Journal of International Conference Proceedings (JICP), 2018)
Supply Chain Management (SCM) has been widely researched in numerous application domains during the last three decades. Despite the popularity of SCM research and applications, considerable confusion remains as to its meaning. There are several attempts made by researchers and practitioners to appropriately define SCM. Most supply chain management (SCM) literature focuses on the manufacturing industry. On the other hand, only little literature on SCM in the service industry whereas very few research papers is on SCM in the academia. This paper represents theory and evolution of Supply Chain Management as well as highlights chronological prospective of SCM in terms of time frame in different areas of manufacturing and service industries. Basic supply chain, from raw material to finished products, for manufacturing and service industries has been demonstrated, including various intermediate parties/organizations. This paper consists of SCM in fishing industry, RMG, textiles are illustrated. Finally, this study illustrates Integrated Tertiary Educational Supply Chain Management (ITESCM) model as the application of SCM in the service industry, which would unlock other applications of SCM in different arenas, particularly service industries. Keywords: Supply chain Management, ITESCM, service industry, education, evolution, SCM